A country in the throes of crime: a theoretical focus on the complexities of kidnapping in Nigeria - Nnam, Macpherson U. (African journal of criminology and justice studies, 2020)
Relying mainly on review of relevant literature to obtain necessary data and information, this research theoretically explored the intricacies of kidnapping in Nigeria. Relative deprivation, frustration-aggression and routine activities theories were integrated to dissect the problem. We found evidence to justify the fact that the crime is on the increase because of the general porous security network and systemic poor economic situation, such as high poverty, unemployment and underemployment rates and their resultant frustration and aggression. Empirical evidence further revealed that politicians equip many jobless, deprived and frustrated youths with lethal weapons during electioneering against their opponents. And many of them were neither disarmed nor engaged in life-improving legitimate livelihood after elections. Thus, availability of arms and ammunition, exposure to aggression and violent behavior, coupled with untold hardship, idleness and lack of capable guardianship, become predisposing factors to kidnapping. It is on this premised that we reached the conclusion that there is a dire need to develop a strong pathway and comprehensive, informative lead/reference material that can assist the government and its policymakers, security agencies and even members of the public in grappling with the complexities of kidnapping. Issues raised suggest a policy direction: that improved general standard of living, particularly meaningful youth socioeconomic empowerment and prosocial political engagements of youths, will suffice in curbing the menace.